Importance of Soil Components in sustainability of Agriculture in Rajasthan - Priyanka Kumari (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Soil forms the backbone of terrestrial ecosystems and is a cornerstone of agricultural productivity, acting as a reservoir for essential nutrients, minerals, and water. The intricate composition of soil—including its physical, chemical, and biological components—directly influences the type and vigour of vegetation that can be supported in any given region. In the Bhilwara district of Rajasthan, soils show significant spatial heterogeneity, ranging from sandy loam and red soils to clay loam and alluvial variants, each imparting unique properties that shape agricultural practices and crop selection. Assessing the intricate links between soil composition and vegetation, this research underscores the central role of soil as both a product of natural processes and a determinant of ecological outcomes. The study employs a combination of field sampling, laboratory analysis, and review of existing literature to evaluate soil characteristics—such as pH, organic matter, texture, and micronutrient status—across representative sites in Bhilwara. Findings reveal considerable variation in soil fertility indicators, with many areas exhibiting low organic carbon and nitrogen, variable phosphorus and potassium levels, and a notable prevalence of micronutrient deficiencies, specifically iron and zinc. These chemical constraints are compounded by the region’s arid and semi-arid climate, which further shapes vegetation patterns and cropping systems. The impact of anthropogenic influences, particularly intensive fertilizer and pesticide use, is also evident, affecting both soil health and the broader agro-ecological balance. DOI: https://doi.org/10.17762/ijisae.v12i16s.7665